Friction-induced slip band relief of -Hadfield steel single crystal oriented for multiple slip deformation; Wear; Vol. 374-375 - Lychagin D. V. Dmitry Vasilievich; Filippov A. V. Andrey Vladimirovich; Novitskaya O. S. Olga Sergeevna; Chumlyakov Yu. I. Yury Ivanovich; Kolubaev Е. А. Evgeny Aleksandrovich; Sizova O. V. Olga Vladimirovna (2017, 2017)
Title screen